Challenges and opportunities of utilizing design thinking in the industry 4.0 era: Based on the case study of industry wastewater treatment system development project process - Hyejin Lee; Yilei Zhang; Huihua Zhang; Xuanchen Liu (Journal of Innovation and Entrepreneurship, 2023)
This paper reviews the research process conducted on developing a new system for industry wastewater treatment application to increase efficiency and sustainability by adopting industry 4.0 technology. The challenge of this project was to (a) utilize the design thinking methodology (human-centered design) entire process; (b) focus on heavy industry rather than the targeted user; and (c) adapt state of art technology. The objective was to revisit and invent new methods, such as metaphoric analysis, body thinking, and organization persona that would contribute to high-level innovative ideas: specifically, (a) the organization persona allowed to understand the dynamics of the complicated stakeholder structure; (b) the role of prototyping was mainly descriptive for communication; and (c) the case's idea generation was used to affect the entire process of the project as well as benchmarking other industries. This paper attempts to address whether it is possible to create a new methodology that would address innovative business opportunities in complicated and high-tech adapting industries.
Keywords: 650; Design thinking; Business model generation; Design-driven innovation; Industry 4.0 technology; Industry wastewater treatment (IWWT)